FACTORS AFFECTING QUALITY OF LIFE FOR THE ELDERLY IN PHON SA SUBDISTRICT ADMINISTRATIVE ORGANIZATION, THA BO DISTRICT, NONG KHAI PROVINCE - Noicharoen, Phunthila (Journal of MCU Nakhondhat, 2022)
The objectives of this research were 1) To study the level of factors affecting the quality of life of the elderly in the Phon Sa Subdistrict Administrative Organization, Tha Bo District, Nong Khai Province; 2) To study the quality of life of the elderly in the Phon Sa Subdistrict Administrative Organization. Tha Bo District, Nong Khai Province. 3) Aanalyzed the relationship between factors affecting the quality of life of the elderly in the Phon Sa Sub-District Administrative Organization, Tha Bo District, Nong Khai Province; and 4) Made recommendations on the improvement of the quality of life of the elderly in the Sub-District Administrative Organization. Phonsa, Tha Bo District, Nong Khai Province. It is a quantitative research. The sample consisted of 230 elderly people or representatives of the elderly by calculating the sample size from Yamane’s formula. The research instruments were questionnaires. The statistics used in the data analysis were frequency distribution, percentage, mean, standard deviation. statistical hypothesis testing Pearson Product Moment Correlation Statistics. The results of the research were as follows: 1) The level of factors affecting the quality of life of the elderly in Phonsa Subdistrict Administrative Organization, Tha Bo District, Nong Khai Province. 2) The level of quality of life of the elderly in Phonsa Subdistrict Administrative Organization, Tha Bo District, Nong Khai Province at a high level. 3) Factors affecting the quality of life of the elderly in the Phon Sa Subdistrict Administrative Organization, Tha Bo District, Nong Khai Province overall were at low level. Can explain 30.60% with an R2 = .306 and an F = 24.848 statistically significant at the .01 level. and 4) Recommendations from the people are that the Sub-district Administrative Organization should arrange public health personnel to provide knowledge about health care for the elderly at the village level.